If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -15 = 48 Reorder the terms: -15 + p = 48 Solving -15 + p = 48 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + p = 48 + 15 Combine like terms: -15 + 15 = 0 0 + p = 48 + 15 p = 48 + 15 Combine like terms: 48 + 15 = 63 p = 63 Simplifying p = 63
| -2(4)-3(-5)= | | 5k+14m+4k+12m= | | 25(x-y)= | | 4-10.00+x=44 | | 7r+20=41 | | 5*3x=12 | | 2x^2+20x+80=0 | | 3w+16=-8 | | -9f-4+8=-32 | | Y=(x-4)(x-2) | | -20+(-2)(-6)= | | r-30=13 | | -9+11x=10x | | 2+(3n+9)=20 | | 9p-13q+12p+19q= | | x+119+x+59=180 | | 15=-3n-3 | | 20+(2)(6)= | | 13f+7g+3f+4g= | | -3(x-1)+2=4 | | X-3x-9+2=21 | | 2y+2=-5+10y | | 8s+4r+13s+6r= | | V=x(24-2x)(24-2x) | | 2y+7-4y=-17 | | x^2+10x-200= | | 9+3*x=-6 | | 75x=2100 | | -5+24x=23x | | 10c+9v+6c-7v= | | 32=18-2k | | -191=-7-8(-5+4a) |